2008
DOI: 10.1007/s10608-008-9192-z
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Control Moderates Relations Between Impulsivity and Bulimic Symptoms

Abstract: The present study, involving 128 undergraduate participants, sought to better understand relations between trait impulsivity, cognitive control, and bulimic symptoms. Three models were contrasted. One model posited that impulsivity and cognitive control would be independent, non-interactive predictors of bulimic symptoms. A second model posited that cognitive control deficits would mediate relations between impulsivity and bulimic symptoms. A third model posited that relations between trait impulsivity and bul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 54 publications
1
10
0
Order By: Relevance
“…Moeller and Robinson (2009) found that men, relative to women, exhibited this tendency to a lesser extent, consistent with men’s greater levels of behavioral impulsivity (e.g., Eagly & Steffen, 1986). Other related findings can be cited as well (Robinson, Ode, Wilkowski, & Amodio, 2007; Robinson, Pearce, Engel, & Wonderlich, 2009). Thus, a cognitive control model of self‐control strength appears to have considerable value, primarily so far from an individual differences perspective.…”
Section: Findings In Support Of the Heuristic Modelmentioning
confidence: 71%
“…Moeller and Robinson (2009) found that men, relative to women, exhibited this tendency to a lesser extent, consistent with men’s greater levels of behavioral impulsivity (e.g., Eagly & Steffen, 1986). Other related findings can be cited as well (Robinson, Ode, Wilkowski, & Amodio, 2007; Robinson, Pearce, Engel, & Wonderlich, 2009). Thus, a cognitive control model of self‐control strength appears to have considerable value, primarily so far from an individual differences perspective.…”
Section: Findings In Support Of the Heuristic Modelmentioning
confidence: 71%
“…One study demonstrated that the interaction between perfectionism and perseveration contributed to increased binge eating, while perseveration alone did not (Short et al, 2013). Another study (not included within the systematic review) found that inhibition moderated the relationship between impulsiveness and binging/bulimic symptoms, but inhibition alone was not correlated with impulsiveness (Robinson, Pearce, Engel, & Wonderlich, 2009). This study did not measure the inhibition of task-set but indicates that the use of interaction terms could contribute to an understanding of how rigidity and transdiagnostic processes relate.…”
Section: Discussionmentioning
confidence: 99%
“…One perspective, generally endorsed in the clinical literature, is that some individuals possess higher levels of cognitive control than others, that is, greater capacities to override dominant response tendencies when the task requires it. This capacity-related perspective has been somewhat generative in clinical literatures (e.g., Morgan & Lilienfeld, 2000) but has often not yielded dividends in understanding personality processes of a normal rather than abnormal type (Robinson, Pearce, Engel, & Wonderlich, 2009;Wilkowski & Robinson, 2010). In the absence of brain damage or clinical dysfunction, instead, it is likely more informative to examine cognitive control flexibility, which can be conceptualized in terms of modulating the cognitive control system in a moment-to-moment manner (Miller & Cohen, 2001).…”
Section: Studymentioning
confidence: 99%